NUTRITIONAL ASPECTS OF NEUROLOGICAL DISEASES - Požar, Hajnalka F (Medicinski časopis, 2020)
Neurodegenerative diseases are one of the most common diseases that have consequences for the functioning of the whole organism. Because they are incurable, efforts to improve health through nutrition are noticeable in all countries. The next paper presents the nutritional aspects of the most common neurological diseases (stroke, Alzheimer’s disease, migraine, autism, epilepsy, autoimmune nerves of the nervous system). In the dietary therapy of neurological diseases, in addition to adequate nutrition rich in fruits and vegetables, the increased use of B and D vitamins, omega 3 and 6 fatty acids is emphasized in order to reduce inflammation and normalization of nerve function. In the diet, it is necessary to avoid simple carbohydrates, processed foods, food additives and alcohol. A ketogenic diet with low carbohydrates and increased fat intake has proven to have a positive effect on the brain’s function of epilepsy, multiple sclerosis, and Alzheimer’s disease and migraine.